Evaluating BRICS as an optimum currency area: insights from SVAR modeling - Marida Nach; Ronney Ncwadi (Cogent Economics & Finance, 2024)
The study evaluates the feasibility of BRICS (Brazil, Russia, India, China, and South Africa) countries to form an Optimum Currency Area (OCA) through the analysis of shock correlation within the OCA framework. Employing a structural vector auto regression (SVAR) model proposed by Blanchard and Quah, the analysis encompasses both external and domestic shocks affecting individual countries. The study employs four variables: world real GDP, domestic real GDP as a proxy for output, the real effective exchange rate, and the inflation rate as a proxy for price level, to estimate the shocks. Subsequent analysis includes ANOVA, impulse response function (IRF), and variance decomposition to discern shock magnitudes, adjustment dynamics, and underlying determinants of variability. Empirical results show that BRICS countries display symmetric responses to external shock, however, with overall different sources of variation in the responses to domestic supply, demand, and monetary shocks. The results of the analysis using the ANOVA test, IRF, and variance decomposition also highlight the nuanced disparities across BRICS countries in terms of demand, and monetary shocks, indicative of differences in transmission mechanisms and policy responses. The study underscores the implication of aligning exchange rate mechanisms and monetary policies in facilitating the convergence of shock levels, thereby fostering economic stability among BRICS countries. This study provides a critical analysis of the feasibility of BRICS countries forming an Optimum Currency Area (OCA) through the application of Structural Vector Auto Regression (SVAR) modeling. By analyzing the correlation and dynamics of both external and domestic macroeconomic shocks, the research highlights significant disparities in how these shocks affect BRICS countries. Despite these differences, the study identifies a strong symmetric response to external shocks. These findings underscore the challenges of aligning exchange rate mechanisms and monetary policies among these diverse economies, yet also reveal the potential for economic stability through coordinated policy responses to symmetric external shocks. This work is pivotal in informing policy decisions on deeper economic integration within the BRICS bloc. It also suggests that with careful policy design, particularly focusing on strengthening economic interdependencies and mitigating asymmetric shock, the BRICS bloc could enhance its economic stability and global influence. Therefore, the study also offers valuable insights into the feasibility of a common currency or enhanced economic integration for emerging economies considering monetary unions in a complex global financial landscape. The study's recommendations provide a roadmap for BRICS countries to navigate the complexities of economic integration, making it a significant contribution to the field of international economics and regional development strategies.
Keywords: 330; Optimum currency area(OCA); structural vectorauto regression (SVAR); shock dynamics; BRICS